Carousel Value Added Tax Fraud: Why It Is Difficult to Face - Burianova, Olga; Urbanek, Jiri Frisons (European Journal of Applied Sciences, 2024)
The paper deals with the issue of carousel fraud on value added tax. It is a well-known fact that the collection of value added tax is threatened by tax fraud. A scenario of possible carousel fraud will be presented in the paper. The research question is: Why it's difficult to face VAT carousel fraud? Based on a simple example of carousel fraud, the opportunities of fraudsters are derived. The hexagon of tax fraud is presented as an entity that defines itself in a crisis interface with the entity of the tax administrator. In the crisis interface, it is possible to examine the risks of value added tax collection. A simple illustrative scenario of carousel fraud and the hexagon of tax fraud suggests that tax collection systems are not able to totally counter carousel fraud.